Peran Kegiatan Literasi Dalam Meningkatkan Minat Membaca Dan Menulis Siswa Kelas Atas diSDN Gumpang 1 - Mitasari, Lea Sakti, Dra. Ratnasari Diah Utami, M.Si., M.Pd (2017)
This research is aimed to know the role of literation activity, obstacle and the school effort to improve reading and writing interest for the high students of SDN Gumpang 1. This research is qualitative descriptive research. The main source of this research is the principal, teachers and students by using collecting data through interview, observation and documentation. The legitimate of the research data is using source and technique triangulation. The data is interatively analized which content of data collection, data reduction, serving data, concluding and verification. Based on the collected data, it is described and analyzed. The writer can infer that; 1) literation activity at SDN Gumpang 1 plays a role in motivating students to love reading and writing, 2) the school obstacles to improve reading and writing interest using literation activity are discipline, student's habit, student's interest, and the method applied by the teacher, and 3) the school effort to improve the students reading and writing interest through literation activity is that the school always gives literation activity socialization, introducing the importance of raising the interest and conducting some contests for students in order to make them to be participated actively.